Study on the Causes and Consequences of Greenwashing at Valin Steel - Cai Yining (SHS Web of Conferences, 2025)
Against the backdrop of accelerated global ESG investment and stricter carbon neutrality policies, the steel industry faces dual pressures of green transformation and economic benefits. This article takes Valin Steel as a case study to analyse the causes and consequences of its “greenwashing” behaviour. The study found that intensified market competition, stricter policy supervision, investors’ preference for green development, and corporate profit pressure are the main external factors driving its exaggeration of environmental performance; management incentive mechanisms and brand strategies constitute internal motivations. Although this behaviour improved the corporate image in the short term, it caused a drop in stock prices, damaged market trust, limited financing, and increased legal risks after being exposed. The study suggests that companies should improve the transparency of information disclosure, optimize environmental investment structure, and improve incentive mechanisms. The government should also strengthen supervision and policy support to guide companies to achieve real and sustainable green development.